Performance Improvement for Weather Wireless Sensor Network by Mixed-Byte Compression Scheme - Al-Alak, Saif (Iraqi Journal of Science, 2024)
A Weather Wireless Sensor Network (WWSN) has many limitations related to node throughput (NT), node power (P), and node energy (E). To address the limitations of WWSN, a mixed-byte LZW scheme is proposed. Mixed-Byte reduces the size of the sensed data by merging every two readings of data from the sensor into a single byte. The merged bytes would be highly frequent, which made them appropriate for compression by the Lempel Ziv Welsh (LZW) scheme. The result shows that the proposed Mixed-Byte-LZW gives the best compression ratio (CR) (0.01) for humidity and the best saving compressing rate (SR) (99%) for humidity and pressure. The simulated result shows that the Mixed-Byte-LZW scheme gives the best NT (580 Kbps) for humidity, the highest power saving (PS) (15.98 Kw) for pressure, and the lowest E (0.39 Kj) for transferring humidity data.